A chaos-based image encryption scheme with a plaintext related diffusion - Chong Fu; Shuai Hou; Wei Zhou; Wen-qi Liu; Dong-liang Wang (2013 9th International Conference on Information, Communications and Signal Processing (ICICS), 2013)
In recent years, chaos-based image encryption technology has been extensively studied to meet the increasing demand for online secure image transmission over open networks. However, many of them suffer from known/chosen plaintext attacks as the diffusion key stream used in those schemes is solely determined by the key. To address this problem, a plaintext-related diffusion strategy is presented in this paper. In the diffusion stage, the key stream elements produced by Chen's chaotic system are circularly shifted under the control of plain pixel. As a result, the key stream is related not only to the key but also to the plain image, which effectively promotes the ability against known/chosen plaintext attack. Moreover, compared with 1-dimensional chaotic maps, the Chen's chaotic system has more complicated dynamical property and number of state variables, which further enhance the security of the cryptosystem. Thorough security analysis is carried out with detailed analysis, demonstrating the satisfactory security of the proposed scheme.